2014
DOI: 10.1002/jssc.201400010
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fungicides in sediments using a dispersive liquid–liquid microextraction procedure based on solidification of floating organic drop

Abstract: A dispersive liquid-liquid microextraction procedure based on solidification of floating organic droplet has been investigated for the determination of fungicides (cyprodinil, difenoconazole, myclobutanil, and spiroxamine) in sediments by HPLC with diode array detection. In the overall extraction process, the extraction solvents can be separated easily from the sample solution, and the experiment time was shortened. Moreover, several parameters such as the type and volume of the extraction solvent and dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Some researchers have pointed out that some fungicides have affected aquatic organisms . In recent years, triazole fungicides have been detected in sediments and water in some areas . It was reported that triazole pesticides can interfere with human endocrine system such as changing in liver function, reducing kidney weight, altering urinary bladder structure, and other potential diseases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have pointed out that some fungicides have affected aquatic organisms . In recent years, triazole fungicides have been detected in sediments and water in some areas . It was reported that triazole pesticides can interfere with human endocrine system such as changing in liver function, reducing kidney weight, altering urinary bladder structure, and other potential diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Triazole fungicides are a class of organic heterocyclic compounds, which have the function of sterilization and plant sediments and water in some areas [4,5]. It was reported that triazole pesticides can interfere with human endocrine system such as changing in liver function, reducing kidney weight, altering urinary bladder structure, and other potential diseases [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment is a very important procedure in OCPs analysis, due to the low abundance of them in environment and the complex matrices. Traditional techniques like LLE and SPE are still widely applied in the analysis of OCPs. The main disadvantages of these methods are their high time consumption and labor intensity, as well as the usage of large quantities of organic solvent.…”
Section: Introductionmentioning
confidence: 99%
“…LPME is the miniaturized implementation of the conventional LLE, in which the amount of organic solvents is greatly reduced. LPME has been performed in different modes, including single drop microextraction (SDME) , headspace LPME , hollow‐fiber (HF) LPME , dispersive liquid–liquid microextraction (DLLME) , and solidified floating organic drop microextraction (SFODME) . LPME has also been the subject of several reviews .…”
Section: Introductionmentioning
confidence: 99%